(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This paper deals with an algorithm for the simulation of Fisher’s equation. In this paper the algorithm is developed with the help of Exponential Modified Cubic B-spline and differential quadrature method for the simulation of Fisher’s Equation. Fisher’s equation combines diffusion with logistic nonlinearity. The numerical simulation of these type of equations is very important as these equations occur in logistic population growth models, neurophysiology and nuclear reactions. Herein, the developed exponential modified cubic B-spline functions based differential quadrature method (EMCB-DQM) is applied on the Fishers’ equation. Some practical problems are solved to check the accuracy and utility of the EMCB-DQM.